Circulating exosomal lncRNAs in patients with chronic coronary syndromes - Meili Zheng; Ruijuan Han; Wen Yuan; Hongjie Chi; Yeping Zhang; Kai Sun; Jiuchang Zhong; Xiaoyan Liu; Xinchun Yang (Archives of Medical Science, 2021)
Introduction The concept of chronic coronary syndrome (CCS) was first presented at the European Society of Cardiology Meeting in 2019. However, the roles of exosomal lncRNAs in CCS remain largely unclear.